Pengaruh Tingkat Naungan yang Berbeda terhadap Karakter Pertumbuhan dan Biomassa Tanaman Bawang Dayak (Eleutherine palmifolia (L.) Merr) - Ekawati, Rina; Saputri, Lestari Hetalesi (Jurnal Hortikultura Indonesia, 2020)
This study aimed to determine the effect of different shading levels on the growth and plant biomass character of Dayak onion. This research was conducted in Sukoharjo village, Ngaglik, Sleman, Yogyakarta from May until September 2020 (5 months). This experiment used a single factor treatment in randomized block design with three different shade levels, namely no shade (0%), 55% and 75% of paranet shade. The treatment was repeated five times so that there were 15 experimental units. Each experimental unit consists of ten plants. The observations were on temperature and relative humidity, sprouting age, plant height, number of leaves, leaf area, and plant biomass components. The results showed that the given of 55% and 75% produced the higher of plant height and leaf area than no shade. Seventy percent shade gave 37.1% higher plant height, while 55% shade gave 41.6% wider leaf area than no shade. The number of leaves and plant biomass components was not affected by shade. Dayak onion can be planted in the land with 55 – 75% shade. Keywords: Eleutherine palmifolia, low light intensity, performance, temperature